Sustainable synthesis of antibacterial 3-aryl-2H-benzo[b,1,4]oxazin-2-ones via SNAr Csp2–Csp2 coupling - Salehzadeh, Fatemeh; Esmkhani, Maryam; Noori, Milad; Javanshir, Shahrzad; Iraji, Aida; Mahdavi, Mohammad (Frontiers in Chemistry, 2024)
Introduction The increasing prevalence of antibiotic-resistant pathogens necessitates the urgent development of new antibacterial agents. Concurrently, synthetic chemistry is moving towards more sustainable practices that minimize environmental impact. This study aims to synthesize 3-aryl-2H-benzo[b][1,4]oxazin-2-one derivatives, including the natural product cephalandole A, using a sustainable approach that avoids metal catalysts. Methods We employed nucleophilic aromatic substitution (SNAr) under microwave-assisted conditions to facilitate the synthesis of the targeted compounds. This metal-free carbon–carbon coupling reaction was optimized for efficiency, yielding good results with reduced reaction times. The synthesized derivatives were then subjected to an in silico molecular docking study to predict their antibacterial potential against key bacterial targets, focusing on the binding affinity and interaction profiles. Results The microwave-assisted SNAr method provided good yields of 55% to 82% and significantly reduced reaction times ranging from 7 to 12 minutes, simplifying the overall workup process. Among the synthesized compounds, 3-(1H-indol-3-yl)-6-methyl-2H-benzo[b][1,4]oxazin-2-one (6b) emerged as a promising candidate, demonstrating favorable binding interactions in the molecular docking studies. Discussion The integration of sustainable synthetic methodologies with in silico screening offers a novel and effective strategy for drug discovery. Our findings highlight the potential of the synthesized compounds as antibacterial agents and emphasize the importance of adopting eco-friendly approaches in pharmaceutical chemistry. This research contributes to the global effort to combat antibiotic resistance by providing new compounds for further biological evaluation.